A Clinical Entity Often Missed—Solitary Rectal Ulcer Syndrome in Children - Thirumal, P.; Sumathi, B.; Nirmala, D. (Frontiers in Pediatrics, 2020)
Background: Solitary Rectal Ulcer Syndrome (SRUS) was a relatively uncommon and easily misdiagnosed clinical entity in children. The diagnosis of this condition was often delayed due to lack of clinical suspicion. Only case series were available and no definitive treatment was postulated. Here, we share our experience of SRUS in our institute and reviewed the literature published so far. Aim: To study the clinical profile and treatment response of Solitary Rectal ulcer Syndrome in Children (SRUS). Materials: The clinical profile and one year follow up response of the diagnosed cases of SRUS over a period of five years was retrospectively collected from medical record department. Results: The median age of presentation among 24 children was 8 years with majority (75%) above 5 years. All children presented with intermittent rectal bleeding with median duration of 5.5 months. The other presenting symptoms documented were hard stool (79%), mucorrhea (70%) and abdominal pain (58%). One child presented with rectal prolapse. On colonoscopy, 46% had single ulcer while another 46% had multiple ulcers and 8% had polypoidal lesion. All lesions were within distal rectum and had characteristic histological pattern. All children were treated with conventional treatment like dietary fibers and laxatives along with toilet training. About 75% children attained remission and 25% had relapse but responded with corticosteroid enema. None required surgery. Conclusion: Conventional treatments itself induce and maintain remission in most of SRUS patients if treatment is instituted at the earliest. Thus, early suspicion and diagnosis is needed to achieve remission.